1991
DOI: 10.1007/bf02599388
|View full text |Cite
|
Sign up to set email alerts
|

Differences in access to zidovudine (AZT) among symptomatic HIV-infected persons

Abstract: The authors conclude that traditionally disadvantaged groups have less access to AZT, the only antiretroviral agent demonstrated to increase survival of patients who have symptomatic HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(49 citation statements)
references
References 16 publications
2
45
0
2
Order By: Relevance
“…[45][46][47][48]50,[53][54][55][56][57] Overall, 14 studies found a negative association between non-white race and antiretroviral use in one or more multivariate analyses. 32,36-39,45-48,52-55 Among these 14, eight studies found only a negative association across all outcomes assessed, 32,[36][37][38][39]45,55,56 and six studies found mixed results depending on the specific outcome measure. 37,45,48,[52][53][54] Three studies found a positive association with at least one antiretroviral use measure, 40,44,48 two of which found either no association 44 or a negative association 48 across a different measure of antiretroviral use.…”
Section: Antiretroviral Usementioning
confidence: 99%
See 4 more Smart Citations
“…[45][46][47][48]50,[53][54][55][56][57] Overall, 14 studies found a negative association between non-white race and antiretroviral use in one or more multivariate analyses. 32,36-39,45-48,52-55 Among these 14, eight studies found only a negative association across all outcomes assessed, 32,[36][37][38][39]45,55,56 and six studies found mixed results depending on the specific outcome measure. 37,45,48,[52][53][54] Three studies found a positive association with at least one antiretroviral use measure, 40,44,48 two of which found either no association 44 or a negative association 48 across a different measure of antiretroviral use.…”
Section: Antiretroviral Usementioning
confidence: 99%
“…29 In a logistic regression model that adjusted for level of illness, injection drug use, gender, and insurance status, whites were more likely to report being offered AZT than non-whites (odds ratio [OR] = 1.73; 95% confidence interval [CI] 1.11, 2.69). 32 McLaughlin et al performed an analysis of data on 366 patients (age Ͼ12 years) with an index AIDS diagnosis in 1989-1991 (limited to AIDS patients who had continuous enrollment in New Jersey Medicaid before the AIDS diagnosis and who had not received any antiretrovirals or PCP prophylaxis during the year prior to an AIDS diagnosis). 37 After adjustment for age, injection drug use, gender, primary source of care, and year of AIDS diagnosis, non-whites were less likely to have had any Medicaid claim for AZT following the AIDS diagnosis than whites (OR = 0.76; 95% CI 0.5, 0.9).…”
Section: Antiretroviral Usementioning
confidence: 99%
See 3 more Smart Citations